Keeping in transit: flexible externalization and the dual logics of transit governance in the Americas - Gandini, Luciana (Frontiers in Human Dynamics, 2026)
This article examines how irregularized migrant transit has become a central tool of contemporary migration governance in the Americas. Drawing on the empirical trajectories of Venezuelan migrants crossing multiple countries under precarious and shifting conditions, the article argues that transit is not merely tolerated or obstructed, but strategically instrumentalized by states and other actors to govern mobility. The analysis of policies such as visa restrictions, bilateral agreements, the instrumental use of administrative permits, and the discretionary application of the law shows that these devices generate prolonged and fragmented mobility. Far from reflecting a failure of migration policies, the findings indicate that the persistence of migrant transit constitutes a functional outcome of a pragmatic governance architecture, embedded in dynamics of flexible externalization and sustained by both state and non-state actors. This regional framework operates under a dual logic: while in the corridor crossing northern South America and Central America transit is promoted as a mechanism to evade reception and protection responsibilities (a pragmatic laissez-passer logic), in Mexico it is used to hinder progress through bureaucratic circuits and indefinite waiting periods (a chutes and ladders logic). Through a multilevel approach that links governmental and other actors' strategies with migrants' trajectories, the article contributes to the literature on the intersection between transit and migration governance in Latin America by empirically conceptualizing transit as a functional component of the regional governance of mobility.